2006
DOI: 10.1016/j.ejcts.2006.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-engineered trachea: History, problems and the future☆

Abstract: SummaryThis review tries to summarize the efforts over the past 20 years to construct a tissue-engineered trachea. After illustrating the main technical bottlenecks faced nowadays, we discuss what might be the solutions to these bottlenecks. You may find out why the focus in this research field shifts dramatically from the construction of a tubular cartilage tissue to reepithelialization and revascularization of the prosthesis. In the end we propose a novel concept of 'in vivo bioreactor', defined as the desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 73 publications
0
35
0
Order By: Relevance
“…They proposed layered scaffolds with a porous catheter within the inner layer of the scaffold for a continuous supply of cells and nutrition media and an outer layer of the construct granting the necessary stability. In contrast to traditional bioreactors in which nutrition media mainly fl ow around the constructs, now a perfusion system was planned within the scaffolds similar to the blood vessel distribution in vivo [104] . This group seeded in a next step a phase -segregated multiblock copolymer (DegraPol  ) [105] with human tracheal epithelial cells and offered a continuous supply of cells and nutrition media via a porous catheter within the scaffolds.…”
Section: Vascular Supply Of Tracheal Constructsmentioning
confidence: 99%
“…They proposed layered scaffolds with a porous catheter within the inner layer of the scaffold for a continuous supply of cells and nutrition media and an outer layer of the construct granting the necessary stability. In contrast to traditional bioreactors in which nutrition media mainly fl ow around the constructs, now a perfusion system was planned within the scaffolds similar to the blood vessel distribution in vivo [104] . This group seeded in a next step a phase -segregated multiblock copolymer (DegraPol  ) [105] with human tracheal epithelial cells and offered a continuous supply of cells and nutrition media via a porous catheter within the scaffolds.…”
Section: Vascular Supply Of Tracheal Constructsmentioning
confidence: 99%
“…84 Although tracheal stenosis is a rare disease, the mortality rates for patients with long-segment tracheal stenosis (abnormal narrowing) and atresia (abnormally closed or absent trachea) are nearly 77 and 100%, respectively, as summarized by Fuchs et al 13 Many issues such as neoplasms, tracheotomy, congenital disorders, prolonged endotracheal intubation, and other types of tracheal trauma affect the tracheal lumen and can cause stenosis or tracheomalacia. As a result, any damage to the trachea can compromise speech, deglutition (swallowing), respiration, mucociliary clearance, and immune protection from inhaled or ingested antigens 24 -all important functions for survival.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it has proven to be extremely difficult to reconstruct the capillary net inside the TE organ (6). Previous studies have demonstrated that implanted TE substitute get the To deal with this technical problem, we designed an "in-vivo bioreactor" design defined as implanted TE airway substitutes perfused with intra-scaffold medium flow created by an extracorporeal portable pump system for in situ organ regeneration (9). In pilot tests, we demonstrated three main advantages of this design.…”
Section: Introductionmentioning
confidence: 99%